2003
DOI: 10.1097/01.tp.0000078898.28399.0a
|View full text |Cite
|
Sign up to set email alerts
|

Dextran sulfate acts as an endothelial cell protectant and inhibits human complement and natural killer cell-mediated cytotoxicity against porcine cells

Abstract: DXS binds to porcine cells and protects them from complement- and NK cell-mediated injury in vitro. It might therefore be used as a novel therapeutic strategy to prevent xenograft rejection and has potential for clinical application as an "EC protectant."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 24 publications
5
58
0
Order By: Relevance
“…Repeated DXS injections did not induce systemic complement depletion, nor did they affect serum levels of anti-hamster Ab. However, we recently demonstrated that DXS acts as an EC protectant and prevents human complement-and NK cell-mediated cytotoxicity towards porcine cells in vitro (14). Here, we show binding of DXS-Fluo to the graft EC one day after cardiac xenotransplantation, supporting our hypothesis that DXS acts locally and might functionally replace HSPG that are known to be shed from the EC surface upon activation (13).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Repeated DXS injections did not induce systemic complement depletion, nor did they affect serum levels of anti-hamster Ab. However, we recently demonstrated that DXS acts as an EC protectant and prevents human complement-and NK cell-mediated cytotoxicity towards porcine cells in vitro (14). Here, we show binding of DXS-Fluo to the graft EC one day after cardiac xenotransplantation, supporting our hypothesis that DXS acts locally and might functionally replace HSPG that are known to be shed from the EC surface upon activation (13).…”
Section: Discussionsupporting
confidence: 84%
“…It was shown in vitro, that porcine EC pretreated with human anti-pig IgM became resistant over the next day to complement-mediated damage (28), and in the hamster-to-rat model Soares and coworkers hypothesized that the gradual exposure of the graft to increasing amount of anti-donor Ab could induce a protective phenotype of EC (29). We reported earlier that DXS does not inhibit human IgM deposition on porcine EC (14). Here, we show that DXS adhered to the activated xenograft endothelium and protected it from complement-mediated damage, but did not suppress Ab deposition and up-regulation of protective genes such as HO-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our results show that glomerular C3 staining was reduced in the DXS group compared with control. Studies have shown that DXS inhibits all three pathways of complement activation and dose-dependently protected pig cells from deposition of human complement, and the EC-protective effect of DXS correlated with binding of the substance to the cells (30). Complement-mediated EC activation and damage have also been demonstrated in the pathophysiology of acute vascular rejection in xenotransplantation (31).…”
Section: Discussionmentioning
confidence: 97%